Raf‐ERK1/2 signalling pathways mediate steroid hormone synthesis in bovine ovarian granulosa cells. Issue 5 (23rd March 2019) - Xu, Dejun; He, Huanshan; Jiang, Xiaohan; Yang, Lulu; Liu, Dinbang; Yang, Li; Geng, Guoxia; Cheng, Jianyong; Chen, Huali; Hua, Rongmao; Duan, Jiaxin; Li, Xiaoya; et al.
Contents: Steroid hormones are required for normal reproductive function of female. The aim of this study was to investigate the role of Raf‐ERK1/2 on steroid hormone synthesis in bovine ovarian granulosa cells. Immunohistochemistry assay showed that both B‐Raf and C‐Raf were expressed in granulosa cells, theca cells and Sertoli cells. The protein expression of Raf or ERK1/2 was clearly decreased by Raf inhibitor GSK2118436 or ERK1/2 inhibitor SCH772984, respectively ( p <  0.05). In addition, western blotting was performed for investigating the crosstalk between Raf and ERK1/2, the data showed that Raf positively regulated ERK1/2, whereas ERK1/2 had a negative feedback effect on Raf. The biosynthesis of oestradiol or testosterone was significantly decreased by treatment with GSK2118436 or SCH772984 ( p <  0.05). Conversely, the progesterone biosynthesis was clearly increased by treatment with those inhibitors ( p <  0.05). Furthermore, the mRNA expression of STAR, aromatase and CYP17 was blocked by Raf‐ERK1/2 signalling inhibition, which oppositely induced the mRNA expression of CYP11 . Together, these findings suggested that Raf‐ERK1/2 signalling pathways mediate steroid hormone synthesis via affecting the expression of steroidogenic enzymes.